(untitled) (Bangladesh Journal of Nuclear Medicine, 2016)
Hemangioma is one of the most common benign liver tumors. They are mostly asymptomatic. Differentiating hemangiomas from malignant tumoral lesions and metastases by a non invasive method is very important. We report a asymptomatic case with incidental finding of a large massive hemangioma occupying almost whole of the right lobe of liver and emphasized its detection by Tc-99m red blood cell (RBC) three phase imaging and localization of the tumor. Bangladesh J. Nuclear Med. 17(2): 153-155, July 2014